2020
DOI: 10.15252/embj.2019103558
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of noise and Her6 levels are optimized by miR‐9, allowing the decoding of the Her6 oscillator

Abstract: Noise is prevalent in biology and has been widely quantified using snapshot measurements. This static view obscures our understanding of dynamic noise properties and how these affect gene expression and cell state transitions. Using a CRISPR/Cas9 Zebrafish her6::Venus reporter combined with mathematical and in vivo experimentation, we explore how noise affects the protein dynamics of Her6, a basic helix‐loop‐helix transcriptional repressor. During neurogenesis, Her6 expression transitions from fluctuating to o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(93 citation statements)
references
References 68 publications
13
80
0
Order By: Relevance
“…We therefore provide evidence that the HES1 dynamics are required for NSCs to exit quiescence in vitro , suggesting that oscillations are needed for cells to transition from one state to another rather than just maintaining a progenitor state. This revised view on the functional significance of HES1 is consistent with previous findings showing that when Her6 (orthologue of mouse HES1 in zebrafish) oscillations are diminished due to the increase of noise, cells are unable to transition from progenitor state to differentiation in zebrafish (Soto et al, 2020) whereas the quality and occurrence of HES5 oscillations in mouse spinal cord increases as cells approach the transition to differentiation (Manning et al, 2019). The significance of HES1 oscillations in controlling the state of quiescence may also have implications in tissue regeneration and in cancer where quiescent cancer stem cells are considered to drive cancer progression and metastasis (Chen et al, 2016; Lee et al, 2020; Phan and Croucher, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…We therefore provide evidence that the HES1 dynamics are required for NSCs to exit quiescence in vitro , suggesting that oscillations are needed for cells to transition from one state to another rather than just maintaining a progenitor state. This revised view on the functional significance of HES1 is consistent with previous findings showing that when Her6 (orthologue of mouse HES1 in zebrafish) oscillations are diminished due to the increase of noise, cells are unable to transition from progenitor state to differentiation in zebrafish (Soto et al, 2020) whereas the quality and occurrence of HES5 oscillations in mouse spinal cord increases as cells approach the transition to differentiation (Manning et al, 2019). The significance of HES1 oscillations in controlling the state of quiescence may also have implications in tissue regeneration and in cancer where quiescent cancer stem cells are considered to drive cancer progression and metastasis (Chen et al, 2016; Lee et al, 2020; Phan and Croucher, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Random pattern (no coupling between cells) has similar rates of differentiation as weak coupling, however, weak coupling strength is advantageous because it allows local in phase synchronisation, which by analogy to global synchronisation ( oscillate as well as the peak-to-trough amplitude increases as cells enter the differentiation pathway (Manning et al, 2019). We have also shown that when the transition from noisy dynamic expression to oscillatory expression does not take place, progenitor cells are unable to downregulate HES levels and differentiate (Soto et al, 2020). We speculate that microclusters may act to select cells for differentiation by a transient increase in oscillation amplitude and the spatial periodicity of microclusters may space out differentiating cells to maintain tissue organisation.…”
Section: Discussionmentioning
confidence: 78%
“…Recent live imaging studies of cell fate decisions during neurogenesis have added a new dimension to this knowledge (Das & Storey, 2012, 2014Manning et al, 2019;Nelson et al, 2020;Soto et al, 2020;Vilas-Boas et al, 2011). They have shown the importance of understanding transcription factor (TF) expression dynamics in real time, including the key transcriptional basic helix-loop-helix repressors Hairy and enhancer of split (HES)1 and 5 (Bansod et al, 2017;Imayoshi & Kageyama, 2014;Ohtsuka et al, 1999), in regulating state transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Determining when and where different isoforms are expressed, and finding any changes in expression in disease situations, is challenging. Use of single molecule fluorescent in situ hybridization (smFISH) techniques, which are being employed successfully in zebrafish (Soto et al, 2020; Stapel et al, 2016) will enable a detailed analysis of different splice forms and provide tissue‐specific cellular localization of the transcripts.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%